Early Identification of Autism Spectrum Disorder in Rural Pakistan: Barriers and Strategies for Timely Diagnosis - Dr Huma Yasir; Ms. Maria Nazir; Ms. Narmeen Naseer (`, 2025)
Early detection of Autism Spectrum Disorder (ASD) plays a critical role in better developmental outcomes, but rural Pakistan poses huge obstacles in the early detection of Autism Spectrum Disorder (ASD). This is an extensive literature study examining these impediments and recommends evidence-based, culturally competent steps in this region. The results incorporate three related areas of barriers. In the first place, the sociocultural determinants contribute to the delay of seeking medical help: these include insufficient level of enlightenment of the population, stigmatization and dependence on traditional healers. Second, a lack of trained experts, insufficient primary care training on developmental screening, and a broken path system of referral flow disseminates the health system barriers. Third, it is the lack of social and geographic accessibility due to poverty and the inaccessibility of an urban diagnostic centre which makes the services inaccessible to the majority of rural families. In order to prevail over such challenges, multi pronged attack is necessary. The strategies proposed are aimed at empowering Community Health Workers (CHWs) in terms of basic developmental surveillance and the introduction of community awareness campaigns. Such initiatives should be accompanied by the enhancement of the primary healthcare system including the introduction of screening into regular visits, task-shifting model and engagement of telehealth technologies. Lastly, a system of care with education reforms and supportive policy is the key to developing a sustainable tiered care. Policymakers, healthcare officials, and other community stakeholders must work together to develop a viable channel of early embracement to ensure timely diagnosis and management of ASD cases, thus enhancing the outcome of many more children in the country who have the disorder. Keywords: Autism Spectrum Disorder, Early Diagnosis, Rural Pakistan, Healthcare Barriers, Community Health Workers, Task-Shifting, Telehealth